Variations in food habit of the Himalayan mahseer - Tor putitora (Ham.) inhabiting the Ganga river system in Garhwal region - Kishore, B; Bhatt, J P; Rawat, V S; Nautiyal, P (Indian Journal of Fisheries, 2011)
Investigations on the food and feeding habits were carried out on the Himalayan mahseer with a view to provide information on how the habits of the fish differ in different tributaries of the Ganga river system. Highest percentage of insect larvae and n3rmphs was found in the stock of Nayar (72.1- 89.8 %) and Saung (76.0-92.0 %). In the Ganga, animal matter accounted for 40-100 %, while in the migratory stock of the Alaknanda it was 76.0-88.07 %. Fish remains were more common in the Ganga stock (2.85-60 %), least in the Saung (0.1-0.8 %) and none in mahseer from Alaknanada and the Nayar. Plant matter (diatoms, green algae and macrophytes) ranged from 0-60 ; 6-20 ; 6.22- 19.3 and 4-8 % in the river Ganga, Saung, Nayar and Alaknanda respectively. Organic debris contributed 6.3 ± 0.71, 3.6 ± 0.0 and 36.0 ± 0.2 % of the diets in the Alaknanda, Ganga, Nayar and Saung respectively. On the basis of the percentage composition of food the fingerlings exhibited a greater degree of omnivorous tendency. However, RLG values (0.42-21.11) indicated their carnivorous tendency. The juveniles and sexually immature individuals were found to be carnivorous. The tendency of omnivorous diet persists in higher age groups (6+). The RLG values increased with increasing length of the fish indicating suitability of gut for omnivorous diet.